1993
DOI: 10.1159/000187450
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucose Utilization in Isolated Rat Soleus Muscle by Pseudouridine: Implications for Renal Failure

Abstract: Pseudouridine (ψ) is an outstanding nucleoside which is not rebuilt into the tRNA once the parent tRNA is broken down, ψ inhibits basal glucose utilization in isolated rat soleus muscle with intact membrane with AD50 42 μmol/l and Cmax 66%. ψ at concentrations found in renal failure patients inhibits both the insulin-and tolbutamide-stimulated glucose utilization. Its inhibitory activity is partially additive with diltiazem inhibition and nonadditive in the case of magnesium depletion. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
1
15
0
3
Order By: Relevance
“…Insulin resistance, associated with hyperinsulinemia, has been extensively studied in ESRD, and several pathogenic factors underlying insulin resistance in ESRD have been proposed, as follows: (1) impaired glucose uptake 2 and glucose transport in uremic muscle, 20 (2) defects in the intracellular pathways of glucose metabolism, 20 (3) abnormalities in oxidative and non-oxidative glucose metabolism, 21 (4) elevated circulating concentrations of FFA and hormones with antagonistic actions on insulin, such as glucagon and growth hormone, and (5) an accumulation of uremic toxins. 22 Although the causes of impaired glucose tolerance (IGT) in this patient might include the above-mentioned factors, we found that anemia was a major pathogenic factor behind her insulin resistance, which is in accordance with the findings of Borissova et al 23 and Mak. 24,25 These studies [23][24][25] showed that insulinstimulated glucose disposal increased by about 50% in HD patients after the correction of anemia by treatment with erythropoietin for 3 to 9 months, by assessment of insulin sensitivity with a hyperinsulinemic euglycemic clamp.…”
Section: Discussionsupporting
confidence: 92%
“…Insulin resistance, associated with hyperinsulinemia, has been extensively studied in ESRD, and several pathogenic factors underlying insulin resistance in ESRD have been proposed, as follows: (1) impaired glucose uptake 2 and glucose transport in uremic muscle, 20 (2) defects in the intracellular pathways of glucose metabolism, 20 (3) abnormalities in oxidative and non-oxidative glucose metabolism, 21 (4) elevated circulating concentrations of FFA and hormones with antagonistic actions on insulin, such as glucagon and growth hormone, and (5) an accumulation of uremic toxins. 22 Although the causes of impaired glucose tolerance (IGT) in this patient might include the above-mentioned factors, we found that anemia was a major pathogenic factor behind her insulin resistance, which is in accordance with the findings of Borissova et al 23 and Mak. 24,25 These studies [23][24][25] showed that insulinstimulated glucose disposal increased by about 50% in HD patients after the correction of anemia by treatment with erythropoietin for 3 to 9 months, by assessment of insulin sensitivity with a hyperinsulinemic euglycemic clamp.…”
Section: Discussionsupporting
confidence: 92%
“…Pseudouridine, an outstanding nucleoside, which is not rebuilt into the tRNA once the parent tRNA is broken down, is another accused factor. Pseudouridine inhibits glucose utilization at the postreceptor level through lowering the intracellular Ca concentration [29] . A nonspecific binding reaction between cyanic acid formed from urea and protein or peptide is called carbamoylation.…”
Section: Retention Of Nitrogenous Compoundsmentioning
confidence: 99%
“…IR did not increase with decreasing kidney function. Of course, this would change in the case of further reduction of kidney function because of accumulation of glucose utilization inhibitors, such as hippurate [18] or pseudouridine [11] accumulating mark edly if the clearance of endogenous creatinine decreased below 0.50 ml/s [11,18] and inhibiting insulin action at the insulin postreceptor level [19,20], Their accumula tion could explain the increased IR just in advanced renal failure. Thus, the participation of other mechanisms could have been suggested in mildly to moderately de creased kidney function.…”
Section: Insulin Resistancementioning
confidence: 99%